Penggunaan Alat Biometrik Sidik Jari sebagai Kontrol Akses dalam Analisis CPTED terhadap Risiko Trespassing di Instalasi Gudang Material Korporasi “X” - Muhammad Naufal Afif; Mohammad Kemal Dermawan (Dinasti Review, 2024)
The study aims to analyze the use of a unimodal biometric scanner with fingerprint geometry capital against the risk of break-in or trespassing as an effective access control. The research was conducted for five months, from January 1 to May 15, 2024. The researchers will assess the effectiveness of this biometric system scheme in access control against break-in (both accidental and intentional), with the CPTED theory as the basis for understanding the phenomenon. The qualitative approach is used with direct observation of the installation ‘A’ at the company ‘X’ in Jakarta, during the period 1 January - 20 May 2024. The results of the research showed that on the unimodal biometric access control system with fingerprints in the ‘A’ installation there were 24 cases of break-in and trespassing. Of the total, 17 cases were false positive, while 7 cases were intentional with 3 cases with no bad intensity and 4 cases with poor intensity. The error lies not in the scanner itself, but in security system modifications, inappropriate usage, and improper placement.